Unscrambling cyanobacteria community dynamics related to environmental factors - Mireia eBertos-Fortis; Hanna Maria Farnelid; Hanna Maria Farnelid; Markus V Lindh; Markus V Lindh; Michele eCasini; Agneta eAndersson; Jarone ePinhassi; Catherine eLegrand (Frontiers in Microbiology, 2016)
Future climate scenarios in the Baltic Sea project an increase of cyanobacterial bloom frequency and duration, attributed to eutrophication and climate change. Some cyanobacteria can be toxic and their impact on ecosystem services is relevant for a sustainable sea. Yet, there is limited understanding of the mechanisms regulating cyanobacterial diversity and biogeography. Here we unravel successional patterns and changes in cyanobacterial community structure using a two-year monthly time-series during the productive season in a 100 km coastal-offshore transect using microscopy and high-throughput sequencing of 16S rRNA gene fragments. A total of 565 cyanobacterial OTUs were found, of which 231 where filamentous/colonial and 334 picocyanobacterial. Spatial differences in community structure between coastal and offshore waters were minor. An epidemic population structure (dominance of a single cluster) was found for Aphanizomenon/Dolichospermum within the filamentous/colonial cyanobacterial community. In summer, this cluster simultaneously occurred with opportunistic clusters/OTUs e.g. Nodularia spumigena and Pseudanabaena. Picocyanobacteria, Synechococcus/Cyanobium, formed a consistent but highly diverse group. Overall, the potential drivers structuring summer cyanobacterial communities were temperature and salinity. However, the different responses to environmental factors among and within genera suggest high niche specificity for individual OTUs. The recruitment and occurrence of potentially toxic filamentous/colonial clusters was likely related to disturbance such as mixing events and short-term shifts in salinity, and not solely dependent on increasing temperature and nitrogen-limiting conditions. Nutrients did not explain further the changes in cyanobacterial community composition. Novel occurrence patterns were identified as a strong seasonal succession revealing a tight coupling between the emergence of opportunistic picocyanobacteria and the bloom of filamentous/colonial clusters. These findings highlight that if environmental conditions can partially explain the presence of opportunistic picocyanobacteria, microbial and trophic interactions with filamentous/colonial cyanobacteria should also be considered as potential shaping factors for single-celled communities. Regional climate change scenarios in the Baltic predict environmental shifts leading to higher temperature and lower salinity; conditions identified here as favorable for opportunistic filamentous/colonial cyanobacteria. Altogether, the diversity and complexity of cyanobacterial communities reported here is far greater than previously known, emphasizing the importance of microbial interactions between filamentous and picocyanobacteria in the context of environmental disturbances.